Factors affecting time of access of in-patient care at Webuye District hospital, Kenya - Maxwell M. Lodenyo; Barasa K. Otsyula; Raymond Downing; Kenneth Yakubu; Miriam Miima; Okoye Ifeyinwa (AOSIS, 2016)
Background: Among many Kenyan rural communities, access to in-patient healthcare services is seriously constrained. It is important to understand who has ready access to the facilities and services offered and what factors prevent those who do not from doing so. Aim: To identify factors affecting time of access of in-patient healthcare services at a rural district hospital in Kenya. Setting: Webuye District hospital in Western Kenya. Methods: A cross-sectional, comparative, hospital-based survey among 398 in-patients using an interviewer-administered questionnaire. Results were analysed using SPSS V.12.01. Results: The median age of the respondents, majority of whom were female respondents(55%), was 24 years. Median time of presentation to the hospital after onset of illness was 12.5 days. Two hundred and forty seven patients (62%) presented to the hospital within 2 weeks of onset of illness, while 151 (38%) presented after 2 weeks or more. Ten-year increase in age, perception of a supernatural cause of illness, having an illness that was considered bearable and belief in the effectiveness of treatment offered in-hospital were significant predictors for waiting more than 2 weeks to present at the hospital. Conclusion: Ten-year increment in age, perception of a supernatural cause of illness(predisposing factors), having an illness that is considered bearable and belief in the effectiveness of treatment offered in-hospital (need factors) affect time of access of in-patient healthcare services in the community served by Webuye District hospital and should inform interventions geared towards improving access.